Characterization of Vancomycin Resistant Enterococcus faecium - M Talebi (Iranian Journal of Public Health, 2007)
Background: To determine the species distribution, updated drug susceptibility patterns and genes conferring resistance in clinical vancomycin resistant enterococcal (VRE) isolates.Methods: Clinical enterococcal isolates collected during 7 months, from September 2005 to April 2006 from hospitalized patients and outpatients were studied. Twenty five VRE were isolated from 450 enterococci samples (5.6%). VRE isolates were subjected to antibiotic susceptibility tests. Genotype of these isolates was determined by PCR.Results: All of the isolates were E. faecium and carried the vanA gene. Antibiotic susceptibility tests showed that the isolates were resistant to ampicillin 25(100%), ciprofloxacin 25(100%), gentamicin 24(96%), erythromycin 25(100%), tetracyclin 10(40%) and chloramphenicol 2(8%).Conclusion: VRE strains were resistant to three antibiotics and were susceptible to new antibiotics linezolid and dalfopristin-quinupristin. Switching to treatment with these antibiotics would relieve the problem for a short time.